Report control Chrysomelids in the experimental field of camu-camu from Embrapa Roraima-Brazil - Abanto Rodriguez, Carlos (2013)
Camu-camu is a native fruit tree of the Amazon, is highly value nutritious and great economic potential due to the high content of ascorbic acid (6112 mg/100 g) present in fruits. Camu-camu, like any other plant, when it becomes cultivated outside their natural environment, loses its ecological balance and, consequently, is attacked by phytophagous and severe insect pests, which cause serious damage to the orchard. In this sense, the aim with this study, reporting the identification and control of insect pests in the cultivation of camu-camu, using different methods to attract and capture. It was observed that the best results were obtained in applying Neenmax®, followed by traps shading of black color screen, furthermore, higher occurrence of insects were recorded belonging to the family Chrysomelidae.